Estudo do metabolismo do ácido 2(131 I), 3,5 triiodo benzóico em soja (Glycine max) - Sant’Anna, R; Ohlrogge , A J; Christian , J E; Breckinridge Jr, C E (Revista Ceres, 2025)
2 (131 I), 3,5 triiodobenzoic acid (TIBA) was applied on field and greenhouse grown soybeans (Harosoy-63) by spraying and by leaf brushing, respectively. Time of application corresponded to the onset of flowering, exception for the late spray experiment when it coincided with the pod filling stage. The TIBA photodecomposition was tested by protecting one field treated plant against sunlight.